ANALISIS FAKTOR DOMINAN SERTA PENGARUH MEDIA LEAFLET DAN POSTER TERHADAP PENGETAHUAN PASIEN DIABETES MILITUS (DM) DI PUSKESMAS TIRTA HARJA BANYUASIN - Lilis Suryani (Universitas Pahlawan Tuanku Tambusai, 2022)
Diabetes Mellitus is one of the most common diseases in various countries, especially developing countries. In general, the world's population is estimated to have a prevalence of Diabetes Mellitus as much as 9% and 4% of them die. The highest prevalence of Diabetes Mellitus sufferers is in Southeast Asian countries with a prevalence of 5.7%, the prevalence of Diabetes Mellitus sufferers in Indonesia is far above Timor Leste with a prevalence of 2.2%, Vietnam as much as 3.6%, Philippines as much as 5%. To reduce the prevalence of Diabetes Mellitus, various efforts have been made, one of which is health promotion. This research is an analytic survey with a cross sectional design and the type of research used is a quasi experiment with a pretest-posttest design. The population in this study were all residents in the working area of ​​the Tirta Harja Banyuasin Public Health Center, totaling 22,826 people. The sample in this study was part of the population in the working area of ​​the Tirta Harja Banyuasin Public Health Center and the sample was taken using the Systematic Random Sampling method. So the sample size in this study was 72 people. The results of the study obtained factors that were significantly related to Diabetes Mellitus (DM), including a history of hypertension, obesity, and smoking. Counseling using leaflets and posters has an effect on increasing the knowledge of Diabetes Mellitus (DM) patients at the Tirta Harja Banyuasin Health Center. Keywords: Diabetes Mellitus, Leaflets, Posters